Orthokeratology to Control Myopia Progression: A Meta-Analysis - Sun, Yuan; Xu, Fan; Zhang, Ting; Liu, Manli; Wang, Danyang; Chen, Yile; Liu, Quan (PLOS ONE, 2015)
Objective To evaluate the clinical treatment effects of orthokeratology to slow the progression of myopia. Methods Several well-designed controlled studies have investigated the effects of orthokeratology in school-aged children. We conducted this meta-analysis to better evaluate the existing evidence. Relevant studies were identified in the Medline and Embase database without language limitations. The main outcomes included axial length and vitreous chamber depth reported as the mean ± standard deviation. The results were pooled and assessed with a fixed-effects model analysis. Subgroup analyses were performed according to geographical location and study design. Results Of the seven eligible studies, all reported axial length changes after 2 years, while two studies reported vitreous chamber depth changes. The pooled estimates indicated that change in axial length in the ortho-k group was 0.27 mm (95% confidence interval [CI]: 0.22, 0.32) less than the control group. Myopic progression was reduced by approximately 45%. The combined results revealed that the difference in vitreous chamber depth between the two groups was 0.22 mm (95% confidence interval [CI]: 0.14, 0.31). None of the studies reported severe adverse events. Conclusion The overall findings suggest that ortho-k can slow myopia progression in school-aged children.